Performance and economic assessment of mechanically integrated parallel hybrid aircraft - Carpentier, Thibault; Zhang, Jinning; van Heerden, Albert S. J.; Roumeliotis, Ioannis (American Society of Mechanical Engineers (ASME), 2022)
In this study, a selection of environmental and economic considerations of mechanically integrated parallel hybrid (MIPH) electric propulsion systems for single-aisle civil transport aircraft are assessed. The environmental assessment focuses on the carbon dioxide and nitrogen oxide emissions with different power management strategies and levels of battery technology. In the economic study, the potential subsidies and tax incentives required to make these aircraft financially viable are determined. To capture the performance results, models of the propulsion systems and airframe were constructed using the Siemens Simcenter Amesim systems modelling software. The operating cost was then computed using adapted direct operating cost estimation methods. Battery replacement was incorporated by using a battery cycle aging model. The results showed that using a battery energy density of 300 Wh/kg will not provide any meaningful benefits. For 600 Wh/kg, fuel savings of up to 3% for missions below 650 nm could be obtained for a PMS where the electrical powertrain operates during takeoff, climb, and cruise. However, the NOx emissions were lowest for the takeoff and climb only PMS, implying a trade-off when selecting a PMS. Based on the cost results, it is determined that taxation on carbon emissions would have to increase at least 50-fold from its current levels for the most optimistic scenarios. Alternatively, considerable subsidies, representing large percentages of the purchase price of the aircraft, will be needed.
Keywords: MIPH; hybrid electric aircraft; performance; CO2; NOx; operating costs; subsidies